Answer:
15
Step-by-step explanation:
when x=6 plug it in to the equation and you would get 2(6)+3 which is 12+3 which is 15
<h3>I'll teach you how solve X/3=-19</h3>
-----------------------------------------------
X/3=-19
Multiply both sides by 3:
3x/3= 3(-19)
Simplify:
x= -57
Your Answer Is x= -57
plz mark me as brainliest :)
<span>0.00996 would be it I just took a quiz like that but good luck</span>
Answer:
Step-by-step explanation:
81
=
3
4
and
27
=
3
3
, so this equation can also be written as
3
4
x
=
3
3
(
x
+
2
)
=
3
3
x
+
6
.
Since the bases are now the same, we can equate exponents to get
4
x
=
3
x
+
6
so that
x
=
6
(technically this equating of exponents requires the fact that exponential functions (with base not equal to 1) are one-to-one functions).
(do u understand?)